ปัจจัยที่มีผลต่อความสำเร็จของสมาชิกสหกรณ์ผู้เลี้ยงปลานิลแปลงเพศในอำเภอเมือง จังหวัดพะเยา - สุพาพร ใจทน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objectives of the present study are to explore tilapia farming methods practiced by members of Sex Reversed Tilapia Farmers’ Cooperative in Mueang District of Phayao Province and to examine the input factor as well as the economic and social circumstances having bearing on the business success of 72 cooperative members. A logit model based on maximum likelihood estimation: MLE procedure was employed to estimate the marginal effect of various predictors of success. The business success was judged by the average net profit per rai of tilapia farming per year from selling two batches of tilapia output. By this criterion, 77.78 % of the cooperative members under study are considered successful in tilapia farming business while the remaining 22.22 % are not successful. The study found the majority of tilapia farmers to be characterized as male, 51- 60 years old, with 4 – 6 years schooling, having less than 5 years experience in tilapia farming, and using 2 laborers for tilapia farming activities. The typical tilapia farm would have 1 – 2 fish raising tanks, with 0.25 – 1 rai area of earth-dug pond serving as fish nursery. The tilapia farmers in our case used similar fish nursery management and fish rearing methods in that they would manage the fish farming themselves and obtained the fry from sale agents of tilapia fry supplier. In most cases, they kept records of feeds used for raising tilapia, allowed stock density at the rate of 5,001 – 6,000 fry per rai, sold the output at 52.46 – 56.74 baht per kilogram, and preferred to sell all tilapias harvested from the rearing tank(s) by the lot without sizing. The members of Sex Reversed Tilapia Farmers’ Cooperative had household debts on the range of 1 – 240,000 baht, and those having large farm size faced the highest average cost per kilogram of tilapia output. Medium sized tilapia farms incurred relatively lower but comparable average production cost in comparison with large farms while small sized tilapia farms spent the least for average production cost per kilogram output. From the analysis on the returns to tilapia farming investment in terms of average net profit per year and average net profit per kilogram output, the small sized farms (less than 5 rai) appeared to get the highest returns, followed by the medium sized farms (more than 5 rai but less than 10 rai), while the large sized farms (more than 10 rai) obtained the lowest returns to investment. The application of logit regression model to establish relationship between specific factor and the business success provided the results that the factors contributing to the success of members of Sex Reversed Tilapia Farmers’ Cooperative in the descending order of importance were business concept in tilapia farming, fish rearing experience, gender, and household debt. Furthermore, the results of logit model application had 83.33 % predictive accuracy regarding the predicting factors of business success.